Sorghum proanthocyanidins - Degree of polymerisation, bioaccessibility and antioxidant properties as influenced by extrusion cooking - Duodu, Kwaku Gyebi (2026)
Thesis (PhD (Food Science))--University of Pretoria, 2018.